Effects of Kangaroo Mother Care on the Physiological, Behavioral, and Psychosocial Outcomes of Preterm Infants in Various Hospitals in Karnataka - Anu Susan; Juby Mol. C. John (International Journal of Women's Health Nursing And Practices, 2024)
Background: Kangaroo mother care (KMC) is a technique that encourages skin-to-skin contact, offering various physiological, behavioral, and psychosocial benefits for preterm infants. The objective is to assess the impact of KMC on the physiological, behavioral, and psychosocial development of premature babies. Study Design: This was a quasi-experimental research investigation. Materials and Methods: A purposive sample of sixty premature infants and their mothers was drawn from neonatal intensive care units (NICUs) according to specific inclusion and exclusion criteria. They were divided into two equal groups: the first group (30) received KMC, while the second group (30) received conventional care. Data was collected using the KMC Assessment Flow Sheet (KMCAFS) and the Mother Bonding Behavioral Scale, with assessments conducted both before and after the intervention. The research was accessible three days a week, five hours each day. The average number of cases collected per week ranged between 3 and 4 preterm newborns and their mothers. Results: The results indicated that there were statistically significant differences in the physiological outcomes of premature infants before and after the application of KMC. In the pre-test, the average score for physiological outcomes was 6.3, with a standard deviation of 2.62. In contrast, the post-test revealed an average pain level of 3.83 and a standard deviation of 1.89. The paired ‘t’-test value obtained 36.29 was significant, and P-value ≤0.05) for heart rate, respiration rate, temperature, and weight increase, respectively. Conclusion: KMC effectively and significantly promoted physiological stability, behavioral organization, and improved psychosocial outcomes of preterm infants compared to those receiving standard care.
Keywords: Kangaroo mother care (KMC); behavioral scale; neonatal intensive care units (NICUs); preterm infants; psychosocial outcomes